Understanding regression analysis an introductory guide - Schroeder, Larry D.; Sjoquist, David L.; Stephan, Paula E. (Newbury Park ; London : SAGE, 1986)
Providing beginners with a background to the frequently-used technique of linear regression, this text provides a heuristic explanation of the procedures and terms used in regression analysis and has been written at the most elementary level.
"A SAGE university paper."
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Regression analysis; Social sciences -- Statistical methods